Retrofitted data centres: a new world in the shell of the old. (1st January 2019) - Jacobson, Kate; Hogan, Mél
Abstract : This contribution looks specifically at the process of redeveloping data centre infrastructure: how the value of past capital investments in the built environment can be preserved and multiplied through further capitalist development. We argue that, while the majority of data centres are not placed in these retrofitted industrial buildings, the ones that are indicate a specific spatial logic within the neoliberal order. We show that retrofitting industrial buildings into data centres is about more than putting inactive capital back to 'work'; it is also about the use of industrial infrastructure as a casing to obfuscate the origins, structure, and workings of the neoliberal project, as metaphorised by the data centres that help to constitute its subjects.